Mitochondrial Dysfunction in Aging and Diseases of Aging - Haas, Richard H. (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This collection of review articles authored by international experts pulls together current information about the role of mitochondria in aging and diseases of aging. Mitochondria are vitally important cellular organelles and undergo their own aging process becoming less efficient in aged animals including humans. These changes have wide-ranging significance contributing to immune dysfunction (autoimmunity and immune deficiency), inflammation, delayed healing, skin and retinal damage, cancer and most of the degenerative diseases of aging. Mitochondrial aging predisposes to drug toxicity in the geriatric population and to many of the features of normal aging. The research detailed in this book summarizes current understanding of the role of mitochondria in the complex molecular changes of aging, moving on to specific diseases of aging. Mitochondrial dysfunction is an important target for development of treatments for aging and disease. The last article details how exercise is a treatment and combats many features of the aging process.